Evaluación del Método de extracción de Alcaloides de las hojas del Chocho (lupinus mutabilis sweet) y su implementación para la elaboración de un gel antibacteriano de uso Aséptico - Huertas Borja, Chistian Alexander (2018)
This project focuses on evaluating the maceration with three different solvents (Water, 97% Alcohol and Chloroform) as a method of sales bases, by applying temperatures dehydration in sheets and evaporating solvents enabling the crystallization of the pasta base of alkaloids for its subsequent implementation in the preparation of an aseptic use antibacterial gel. There is a great waste of leaves in the production areas and the inappropriate use of waste obtained from the process of “desamargado” of the plant beads, These anti-nutritional compounds are present in all plant physiology allowing even naturally repel the presence of pests and diseases that may be susceptible during their development, these compounds can be used for the development of phytomedicines, thanks to its aseptic, bactericidal and cicatrizant properties containing these compounds. Through a qualitative analysis which was carried out externally in an accredited laboratory (LABOLAB), it showed the presence of alkaloids in different liquid extracts obtained from the maceration of the leaves, resulting in the presence of these compounds in non-polar solvents and absence in polar solvents. In addition it was found that the best retrieved treatment was treatment number four (N°4) established by: (35° C of dehydrating of the leaves for 10 hours, macerated in water and added magnesium sulfate) since this presented the best performance obtained in extraction then apply it within the aseptic gel formulation. We obtained an aseptic characteristic of the alkaloids of “chocho” yellowing gel, and easily absorbed in the skin according to the thrown results in physico-chemical analysis, also applied an analysis of validation of the product in which it was observed that the concentration of alkaloids and the proportion of alcohol influence the elimination of bacteria on the surface of the hands.